ADJUSTMENT OF MUALAF ADOLESCENCE - Rizqa Andhini; Zaenal Abidin; Dinie Ratri Desiningrum (Faculty of Psychology, Diponegoro University, 2012)
Mualaf are individuals who converted to Islam. The threat of expulsion, termination of financial support, even the threat of termination of kinship is a potential conflict experienced mualaf. This problem has been very heavy when the perpetrators are adolescence because adolescence is an age-prone and unstable. Mualaf adolesence had to adjust to a new religion, and all the changes that accompany. The main objective of this study was to understand the adjustment experienced by mualaf adolescence.The method used is phenomenology. The sample consisted of three subjects who converted to Islam. Two of the subjects before Catholic and one another Hindu. The primary method of data collection is the depth interviews, while supporting the method used is the observation and recording of the interview.The results of this study found that adolescence who commit religious conversion as a strong belief in themselves, are not experiencing difficulty in aligning individual needs with present conflicts related his conversion. Dominant issues that arise in the adolescence self converts is a family matter. Parents and family rejection, feelings of guilt in parents and anxiety of the threat that comes from the parents is a problem that is present in adolescences who decide to convert religions.Adjustment made to the various changes and demands of the present is the way a normal adjustment, the adjustment through self-control, learning, substitution, planning and exploitation of personal abilities. As a defense mechanism that appears in the subject was withdrawn, regression and rationalization, but not dominant. Religiosity, peer support, and the presence of other significant social acceptance is a contributing factor that makes teens converts able to adjust well.